Tourism and growth in european countries: an application of likelihood-based panel cointegration - de Mello-Sampayo, F.; Vale, S. (Annual Meeting of the Portuguese Economic Journal, 2011)
This paper applies likelihood-based panel cointegration techniques to examine the existence of a long run relationship between GDP, tourism earnings per tourist and total trade volume for a panel of European countries over the period 1988-2010. Removing the cross dependency, our panel tourism-led growth model indicates that tourism development has a higher impact on GDP in the South than in North European countries. The policy implication of this result is that for this group of countries, the best strategy is to raise tourism receipts. Furthermore, the volume of trade shows a significant and much more stronger effect on the long run economic growth in our sample economies than tourism does.